The Effect of Fasting Ramadhan and Diet on Blood Sugar Levels in People With Diabetes Mellitus : A Literature Review - Suherman Suherman; Rehan Aula Salsabila; Andriyani Asmuni; Dihartawan Dihartawan; Munaya Fauziah; Triana Srisantyorini; Najwa Khairina; Dina Rahma Fadlilah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
ABSTRACT Diabetes mellitus is a health disorder caused by an increase in blood sugar levels due to insulin resistance. Fasting can be used as a way to control diet, when fasting calories in the body will be reduced and the body will break down glycogen into glucose so that glucose levels can decrease. The purpose of this paper is to determine the effect of Ramadan fasting and eating patterns on blood sugar levels in people with diabetes mellitus. The method used with the literature review is by reviewing several journals about the effect of fasting Ramadan and diet on blood sugar levels in people with diabetes mellitus. The results of this paper show that fasting has a significant effect on reducing blood sugar levels in Diabetes Mellitus patients. Decreased blood sugar levels are also influenced by diet. The conclusion of this writing shows that there is an influence on the decrease in blood sugar levels in people with diabetes mellitus who carry out Ramadan fasting. Then in the relationship between eating patterns, there is a relationship between diet and the incidence of diabetes.